2019
DOI: 10.1152/ajpheart.00654.2018
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous ubiquitin reduces inflammatory response and preserves myocardial function 3 days post-ischemia-reperfusion injury

Abstract: β-Adrenergic receptor (β-AR) stimulation increases extracellular levels of ubiquitin (UB) in myocytes, and exogenous UB decreases β-AR-stimulated myocyte apoptosis and myocardial fibrosis. Here, we hypothesized that exogenous UB modulates the inflammatory response, thereby playing a protective role in cardiac remodeling after ischemia-reperfusion (I/R) injury. C57BL/6 mice infused with vehicle or UB (1 μg·g−1·h−1) were subjected to myocardial I/R injury. Functional and biochemical parameters of the heart were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 68 publications
(79 reference statements)
0
22
0
Order By: Relevance
“…Exogenous ubiquitin plays a protective role in attenuating the cardiac inflammatory response and decreasing infarct size after I/R injury. Moreover, exogenous ubiquitin increased the expression of MMP-2 and MMP-9, which can increase ECM degradation and can contribute to a reduction in infarct size [54]. Extracellular ubiquitin interacts with CXCR4 and affects the proliferation of cardiac fibrosis via the ERK 1/2 pathway [55,56].…”
Section: The Role Of the Adaptive Immune System Focused On T Cells Asmentioning
confidence: 99%
“…Exogenous ubiquitin plays a protective role in attenuating the cardiac inflammatory response and decreasing infarct size after I/R injury. Moreover, exogenous ubiquitin increased the expression of MMP-2 and MMP-9, which can increase ECM degradation and can contribute to a reduction in infarct size [54]. Extracellular ubiquitin interacts with CXCR4 and affects the proliferation of cardiac fibrosis via the ERK 1/2 pathway [55,56].…”
Section: The Role Of the Adaptive Immune System Focused On T Cells Asmentioning
confidence: 99%
“…A previous study reported that a substantial increase in MMP9 and MMP2 expression levels was positively correlated with the degree of left ventricular fibrosis in a mouse model of pressure overload ( 23 ). Additionally, a previous study demonstrated that MMP9 and MMP2 expression levels were significantly increased in myocardial I/R model mice compared with sham mice ( 24 ). In the present study, compared with sham rats, MMP9 and MMP2 mRNA and protein expression levels were significantly increased following myocardial I/R injury, but significantly reduced following Ad-hTK1/hTIMP1 injection.…”
Section: Discussionmentioning
confidence: 96%
“…During IRI, the sudden release of oxygen molecules reactivates mitochondria and the electron transport chain, resulting in a significant increase in reactive oxygen species synthesis and activation of MMP-2 [ 26 ]. MMP-2 was proved to promote the degradation of cardiac troponin I and promote apoptosis, and inhibition of MMP-2 was helpful to prevent apoptosis [ 27 ]. Previous study also showed that MMP-2 was involved in the process of ventricular remodeling in HF, and is an independent predictive factor of death [ 28 ].…”
Section: Discussionmentioning
confidence: 99%